Outsourcing vs. shared services model - Płoneczka, Karolina (Economics of the 21st Century, 2017)
Outsourcing is one of the most popular phenomenon in today’s global economy. It can be defined as handing over some processes or services to an external company. In contrast shared services model is based on providing certain service by one part of the organization to the other parts, most commonly used in case of HR or IT services, but also payroll, accounting and others. The goal of this article is to describe briefly these two phenomena, showcase the examples from the international business environment and in the end compare these processes. Shared services model is mostly focused on optimizing: people, capital, time and other corporate resources. Shared services sector is developing rapidly in Poland thanks to highly-skilled workforce, good infrastructure and competitive labor costs. South-east Asia remains top outsourcing destination in the world, Cracow is ranked on 8th place among top outsourcing destinations in the world. The main research method used for this article is literature study
Ekonomia XXI Wieku = Economics of the 21st Century, 2017, Nr 4 (16), s. 77-86
Keywords: outsourcing; shared services model; shared services center (SSC); model usług wspólnych; centrum usług wspólnych